Internal and External Shocks and Economic Policy Innovations in Bolivia: A General Approach - Rivero, Roger Alejandro Banegas; Ramirez, Marco Alberto Nunez; Vargas, Jorge Salas; Caba, Luis Fernando Escobar; Garcia, Irma Guadalupe Esparza (Asian Economic and Financial Review, 2021)
This paper contributes to quantifying the severity of various types of shocks for one small open economy. The role of fiscal policy was evaluated along with monetary and exchange rate innovations and the findings reflect the relevance of domestic and external shocks. These estimates show that productivity shocks explain about 90% of real variables in the economy. Regarding external shocks, the presence of oil perturbance affects approximately one-third of the fiscal balance behavior. Finally, the main instrument of economic policy is related to public investment innovations that cause more than the 50% of the real variables, especially as an instrument for economic crisis.